A checklist of the extant species of ophiuroids (Echinodermata: Ophiuroidea) from Brazilian waters - de Moura Barboza, Carlos Alberto; Borges, Michela (Zootaxa, 2012)
Species of ophiuroids in Brazilian waters were last compiled over a decade ago. Since that time, there have been manyimportant contributions with additional diversity and species distribution data. An updated review of the number of records isnecessary, as well as an identification of the gaps related to the taxonomy. We list a total of 133 species that belong to 54genera and 16 families. This number corresponds to approximately 6% of the species described worldwide. All families havebeen registered, and the majority of species belongs to the family Amphiuridae (50spp), which have primarily been recoveredduring surveys of the shallow waters of the continental shelf. On the other hand, numerous new records (e.g. species belongingto the families Ophiacanthidae and Ophiuridae) have been registered in recent years from the deeper margins of Brazil. Asophiuroids are an abundant component of the benthic fauna, increasing occupation of coastal areas and the exploration of energy and mineral resources in the deep sea call for a better knowledge about the diversity and biogeography of the group.